Media Sosial untuk Penguatan Fungsi Pelayanan - Muhammad Imam Wahyudi; Teguh Ilham (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2021)
The Covid-19 pandemic requires changes quickly, including the aspect of public services. The current situation hinders the community to get services directly, one of which is from kelurahan (the sub-district office). This community service aims to provide training to kelurahan officials and the community in optimizing the use of social media in providing administrative services and receiving suggestions,critics, or complaints from the community. This mentoring activity was carried out through limited face-to-face meetings at the Kelurahan Madatte office by adhering to the covid protocol. The activity resulted in a positive response, both kelurahan service officers and users where various information services could beaccessed through the WhatsApp official account of Kelurahan Madatte. Although the available menus are still limited to the three services, namely: kelurahan address, administration services, and kelurahan’s social media accounts, it is hoped that after this training, kelurahan service officers will be able to innovateto develop this system by adding other features. In addition, this innovation is expected to trigger local and national governments to provide more advanced technology assistance and budgets so that every smallest government unit which is also a service unit that is very close to the community can provide optimalservices to the community.